Modelling metadata in central banks - David Bholat (European Central Bank (ECB), 2016)
This article discusses a small scale pilot to harmonise three Bank of England statistical and regulatory data forms. The primary purpose of the pilot was to assess opportunities for improved operational efficiency in regulatory reporting. The broader purpose was to demonstrate how common data standards can be created from heterogeneous data sets. In the course of discussing the pilot, the article explains the history of how data has been collected at the Bank of England; how that process is changing in light of the Bank's Strategic Plan; and why a common data standard is a critical financial market infrastructure fundamental to the success of global regulatory reform.
Keywords: E58; C81; G18; 330; Bank of England; central banks; data standards; metadata; regulatory reporting